2023
DOI: 10.1177/15330338221146024
|View full text |Cite
|
Sign up to set email alerts
|

RhoA G17E/Vav1 Signaling Induces Cancer Invasion via Matrix Metalloproteinase-9 in Gastric Cancer

Abstract: Background: RAS homolog family member A (RhoA), a member of the Rho family of small GTPases, and Vav1, a guanine nucleotide exchange factor for Rho family GTPases, have been reported to activate pathways related to the actin cytoskeleton and regulation of cell shape, attachment, and motility. The interaction between these molecules in lymphoma is involved in malignant signaling, but its function in epithelial malignancy is unknown. Here, we investigated the malignant signal of mutant RhoA in gastric cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Ectopic expression RhoA mutant G17E induced morphological changes, involving the formation of a spindle shape and sharp edges, but did not alter growth in GC cells. G17E upregulated Vav1 expression and facilitated the invasion of GC cells via MMP-9, implying that RhoAG17E/VAV1 signaling could be a potential therapeutic target for GC [ 50 ]. Rho GDP differentiation inhibitor 2 (RhoGDI2) can enhance invasion via the Rac1/Pak1/LIMK1 pathway [ 51 ].…”
Section: Signaling Pathways Involved In Gc Invasion and Metastasismentioning
confidence: 99%
“…Ectopic expression RhoA mutant G17E induced morphological changes, involving the formation of a spindle shape and sharp edges, but did not alter growth in GC cells. G17E upregulated Vav1 expression and facilitated the invasion of GC cells via MMP-9, implying that RhoAG17E/VAV1 signaling could be a potential therapeutic target for GC [ 50 ]. Rho GDP differentiation inhibitor 2 (RhoGDI2) can enhance invasion via the Rac1/Pak1/LIMK1 pathway [ 51 ].…”
Section: Signaling Pathways Involved In Gc Invasion and Metastasismentioning
confidence: 99%
“…Another mechanism of action of VAV1 involvement emerged from studies in gastric tumors that showed that the ectopic expression of the RHOA mutant G17E in the human gastric cancer cell line MKN74 triggers VAV1 expression at the mRNA and protein levels, promoting cell migration and invasion [84]. RHOA G17E has been shown to promote cell invasion through VAV1 in vivo in a nude mouse peritoneal xenograft model [84]. This study raises the possibility that VAV1 acts on tumorigenesis through its association with the proteins of the RHO/RAC GTPase signaling pathway.…”
Section: Vav1 Ectopic Expression In Human Tumorsmentioning
confidence: 99%